2013
DOI: 10.1371/journal.pone.0080280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Cardiac Differentiation in Mouse iPS Cells: Role of Hypoxia Inducible Factor-1 and Wnt/Beta-Catenin Signaling

Abstract: BackgroundDisturbances in oxygen levels have been found to impair cardiac organogenesis. It is known that stem cells and differentiating cells may respond variably to hypoxic conditions, whereby hypoxia may enhance stem cell pluripotency, while differentiation of multiple cell types can be restricted or enhanced under hypoxia. Here we examined whether HIF-1alpha modulated Wnt signaling affected differentiation of iPS cells into beating cardiomyocytes.ObjectiveWe investigated whether transient and sustained hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…For example, we demonstrated here that, in the presence of an antagomiR blocking mir-499, expression of APC was significantly increased (more than 2-fold), presumably causing a depletion in β-catenin 50 . Alterations in β-catenin-dependent Wnt signaling have been demonstrated under certain cardiac conditions, such as hypoxic conditions during differentiation of mouse pluripotent stem cells to beating cardiomyocytes, hypoxia activated Wnt signaling and impaired cardiomyocyte differentiation 75 . Furthermore, Wnt has been shown to enhance apoptosis in cardiomyoctes 76 suggesting a plausible mechanism for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we demonstrated here that, in the presence of an antagomiR blocking mir-499, expression of APC was significantly increased (more than 2-fold), presumably causing a depletion in β-catenin 50 . Alterations in β-catenin-dependent Wnt signaling have been demonstrated under certain cardiac conditions, such as hypoxic conditions during differentiation of mouse pluripotent stem cells to beating cardiomyocytes, hypoxia activated Wnt signaling and impaired cardiomyocyte differentiation 75 . Furthermore, Wnt has been shown to enhance apoptosis in cardiomyoctes 76 suggesting a plausible mechanism for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen levels were maintained at 30% DO saturation to support the hiPSC growth during the expansion phase and early differentiation phase as shown in a previous publication [47]. Reports showed that hypoxia activated the expression of hypoxia inducible factor (HIF-1), which may indirectly enhance cardiomyocyte differentiation by the activation of a number of growth factors (such as VEGF) that have a synergistic effect on mesodermal cardiogenesis [18,43,49,51]. Further work is required, however, to optimize DO level during the different phases of the bioprocess system in order to improve the overall efficiency of CM generation.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the HIF-1 signaling pathway, known to reduce the number and the maturation of differentiating cardiomyocytes, is specifically targeted by miRs during the reprogramming process of SStCs. Of note, HIF-1 signaling appears to impair cardiogenic differentiation by reducing the number and the maturation of differentiating cardiomyocytes, which might provide a possible explanation of the lower cardiac differentiation capabilities observed in S-iPSCs (47). Finally, among the commonly targeted pathways, the PI3K/Akt pathway can be involved in the molecular mechanisms regulating cardiomyogenesis specifically by suppressing the GSK-3β activity and maintaining the Wnt/beta-catenin activity (48).…”
Section: Discussionmentioning
confidence: 99%